Answer:
x = 0
Step-by-step explanation:
Solve for x:
1.2 (5 - x) = 2 (1.4 x + 3)
Expand out terms of the left hand side:
6 - 1.2 x = 2 (1.4 x + 3)
Expand out terms of the right hand side:
6 - 1.2 x = 2.8 x + 6
Subtract 2.8 x from both sides:
6 + (-1.2 x - 2.8 x) = (2.8 x - 2.8 x) + 6
-1.2 x - 2.8 x = -4 x:
-4 x + 6 = (2.8 x - 2.8 x) + 6
2.8 x - 2.8 x = 0:
6 - 4 x = 6
Subtract 6 from both sides:
(6 - 6) - 4 x = 6 - 6
6 - 6 = 0:
-4 x = 6 - 6
6 - 6 = 0:
-4 x = 0
Divide both sides of -4 x = 0 by -4:
(-4 x)/(-4) = 0/(-4)
(-4)/(-4) = 1:
x = 0/(-4)
0/(-4) = 0:
Answer: x = 0